Pengaruh Harga, Kualitas Pelayanan dan Kecepatan Pengiriman terhadap Keputusan Menggunakan Jasa Kurir Sicepat Express Cabang Bireuen - Saddam, Muhammad; Iskandar, Raihan (Singkite Journal, 2023)
This research aims to prove the existence of a link in the form of (a) a causal relationship between shipping price factors, service and delivery speed of the Sicepat Express Bieuen Branch courier service. (b) The direct and indirect influence of each factor of delivery price, service quality and delivery speed on consumer decisions for the Sicepat Express Bieuen Branch courier service. A survey of 50 consumers and analysis using a statistical path model shows:(1) there is a relationship The causal category is quite close between the variables of delivery price and service quality, namely 0.523, the relationship between service quality and delivery speed is in the medium category (0.421) and the relationship between delivery speed and price is in the quite close category (0.522). (2) It is proven that there is a significant direct and indirect influence of shipping price factors on consumers' decisions to use the Sicepat Express Courier service, Bireuen Branch, amounting to 45.16%. Meanwhile, the direct and indirect influence of service quality on consumer decisions to use courier services is 43.79%. And the direct and indirect influence of delivery speed on consumers' decisions is 37.29%. (3) Simultaneously price, service quality and delivery speed have a positive influence on consumers' decisions to use the Sicepat Express Courier service, Bireuen Branch, with a contribution of 61.3%.